Color Atlas of Histopathology - Curran, R. C. (London, England : Oxford University Press, 1985)
This is the fourth edition of Professor Curran's well-known and widely used colour atlas of histopathology. The text has been completely revised and there have been additional immunohistological images added to the 804 full colour illustrations that make the atlas such a valuable reference text for students and pathologists alike. The clarity of the text and the colour balance of the sharply-focused illustrations are unique. The contents of each illustration were carefully chosen and balanced for the structural importance. The boundaries of the pictures are defined with precision, to make sure that very little space is wasted in the tissues. The general arrangement of the contents has been retained, with a chapter on each of the main systems or organs of the body. There is an introductory chapter of a general nature which demonstrates the more important reactions of the tissues in disease and at the same time teaches the student the basic language of histopathology, thereby enabling him or her to read and assess the significance of changes in the tissue as revealed by microscopy. Most of the conditions are common or fairly common diseases, but occasional rare lesions are included. This book is primarily an atlas, the primary purpose of which is to convey information in visual form. It is meant to complement existing textbooks. A new comprehensive index has been prepared for this edition. The book is intended primarily for undergraduate students but experience with its predecessors suggests that it is likely to prove useful to postgraduate students in training in pathology or other clinical disciplines.
In English
Keywords: Histology, Pathological -- Atlases; Pathology -- atlases